Adsorption of algal organic matter on activated carbons from alternative sources: Influence of physico-chemical parameters - Leite, Luan de Souza; Hoffmann, Maria Teresa; de Vicente, Fábio Simões [UNESP]; dos Santos, Danilo Vitorino; Daniel, Luiz Antonio (Elsevier, 2021)
The algal organic matter (AOM) is a concern for water treatment due to its low removal by traditional technologies. Granular activated carbon (GAC) is used extensively in drinking water treatment in various roles; however, there is little information about GAC performance for AOM removal. In this context, this study investigated the AOM removal by alternative (bovine bone (BO), babassu coconut (BA), and dende coconut (DE)) and traditional (bituminous (BI)) activated carbons in different testing conditions (pH, ionic strength, and adsorbent dosage). Freundlich model fitted better to predict the isotherm data than the Langmuir model for all GACs (R2 > 0.99). High removals were found for BI (86.3 to 99.5%), BA (82.9 to 95.5%), BO (67.2 to 88.2%), and DE (58.0 to 78.8%). The AOM removal followed the order of BI > BA > BO > DE for all conditions tested. The traditional BI showed the best performance for AOM removal; however, BA was also effective and showed efficiencies close to BI. Trihalomethanes formation potential (THMFP) after the adsorption was assessed and high reductions were obtained for BI (86.3 to 99.5%), BA (82.9 to 94.3%), BO (67.2 to 88.2%), and DE (58.0 to 78.8%). The competition between AOM with dissolved humic acid (HA) for sorption sites was also evaluated. The presence of HA in a lower concentration than AOM can increase the AOM removal significantly for all GACs, making their efficiencies very similar. Our findings will allow a better design to improve the affinity of these GACs for AOM removal in water treatment facilities.
Keywords: Adsorption; Competitive adsorption; Granular activated carbon; Natural organic matter; Trihalomethanes